2020
DOI: 10.1111/nyas.14430
|View full text |Cite
|
Sign up to set email alerts
|

Do preliterate children spontaneously employ spatial coding for serial order in working memory?

Abstract: The ability to memorize arbitrary sequences contributes to cognitive faculties like language and mathematics. Research suggests that in literate adults, serial order in verbal working memory (WM) is grounded in spatial attention and is mentally organized according to our reading habits, that is, from left-to-right in Western cultures. Currently, it is unknown whether spatialization is a consequence of literacy, or whether the ability already exists early in life but is shaped by literacy in "calibrating" the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…This pattern almost completely reversed in the present study where seven (among 29) participants showed a right-to-left SPoARC effect (two of them showed a left-to-right SPoARC). In addition, the pattern we present here was close to that reported in Guida et al, 36 where six (among 19) right-to-left reading participants exhibited a rightto-left SPoARC and two a left-to-right SPoARC (see the bootstrapping analysis run by van Dijck et al 47 ), despite the fact that both experimental setups were different (i.e., in Guida et al, 36 participants had to memorize the color of four squares).…”
Section: Flexibility and Wm Spatializationsupporting
confidence: 90%
See 4 more Smart Citations
“…This pattern almost completely reversed in the present study where seven (among 29) participants showed a right-to-left SPoARC effect (two of them showed a left-to-right SPoARC). In addition, the pattern we present here was close to that reported in Guida et al, 36 where six (among 19) right-to-left reading participants exhibited a rightto-left SPoARC and two a left-to-right SPoARC (see the bootstrapping analysis run by van Dijck et al 47 ), despite the fact that both experimental setups were different (i.e., in Guida et al, 36 participants had to memorize the color of four squares).…”
Section: Flexibility and Wm Spatializationsupporting
confidence: 90%
“…This is repeated 5000 times. Subsequently, we established confidence intervals based on the range in which mid 80% of the bootstrap slopes were located (we used the same confidence level than van Dijck et al 47 . to allow direct comparison with this study).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations